Analysis of Junction Congestion and ITS Handling Efforts on Urban Roads - Gde Ngurah Purnama Jaya; Umar Mansyur (Publikasi Indonesia, 2024)
Congestion is one of the problems that often occurs in several areas, such as the Damage Circle Line Intersection. This research aims to identify the causes of traffic problems, the characteristics of traffic movements, and the level of service in the area. The research method was carried out by collecting related data from the results of literature studies, agency surveys, and observations. There are several transportation problems at the Damage Circle Line Intersection. The Damage Circle Line Intersection has transportation problems because of the road capacity and vehicle and other commonly known as conflict points. In addition, the traffic light is not functioning properly, and the level of road service is quite low, indicating that road service is quite high, while the travel speed is low.